Career Adaptability of Female High School Students in Islamic Boarding Schools in Yogyakarta: An Empirical Analysis and Career Development Challenges - Sarah Salsabila; Aprilia Tina Lidyasari; Afanin Halqim (Indonesian Journal of Counseling and Development, 2026)
The career adaptability of female high school students in Islamic boarding schools is a crucial aspect of building their readiness to navigate complex workforce dynamics. However, empirical studies focusing on this specific demographic remain remarkably scarce. This study addresses this literature gap by quantitatively assessing career adaptability levels to understand their unique developmental needs. Employing a descriptive quantitative design, data were collected from 175 female high school students across four Islamic boarding schools in Yogyakarta. The assessment utilized the Indonesian Career Adapt-Abilities Scale (ID-CAAS). Descriptive statistical analysis reveals that the overall career adaptability of these students predominantly falls within the moderate category (42.3%). Notably, while the students exhibited strong capacities in the concern and confidence dimensions, indicating a positive future orientation and self-belief significant vulnerabilities emerged in their autonomy and exploration. Specifically, 38.3% of the students scored in the low to very low categories for the control dimension, and 30.2% for the curiosity dimension. These empirical findings expose a critical readiness gap. Despite possessing a foundational awareness of their future, the students significantly lack the independent decision-making skills and exploratory initiative necessary for optimal career development. This limitation is heavily influenced by the restrictive environment and hierarchical culture of the boarding schools. Consequently, this study concludes that conventional career guidance methods are insufficient. It underscores the urgent need to design structured, context-sensitive interventions, such as independent career exploration media and community-facilitated guidance, to optimally strengthen the career autonomy and adaptive readiness of female high school students in Islamic boarding schools